Colonial Project, National Game : a History of Baseball in Taiwan - Morris, Andrew D. (Asia Pacific modern., 2011)
In this engrossing cultural history of baseball in Taiwan, Andrew D. Morris traces the game's social, ethnic, political, and cultural significance since its introduction on the island more than one hundred years ago. Introduced by the Japanese colonial government at the turn of the century, baseball was expected to "civilize" and modernize Taiwan's Han Chinese and Austronesian Aborigine populations. After World War II, the game was tolerated as a remnant of Japanese culture and then strategically employed by the ruling Chinese Nationalist Party (KMT) Even as it was also enthroned by Taiwanese.